IMPLEMENTASI THEORY OF CONSTRAINTS PADA UPAYA PENINGKATAN KAPASITAS PRODUKSI OLAHAN BANDENG, DI KOTA BEKASI - Docki Saraswati; Rosiyana Dewi; Sucipto Adisuwiryo (JURNAL TEKNIK INDUSTRI, 2016)
Competition in finding jobs increasingly tight, encourages efforts to establish its own selfemploymentby utilizing available resources. Research conducted on entrepreneur processedbandeng fish in Bekasi, which produces ‘otak-otak bandeng’. SWOT analysis approach conductedon aspects of production, finance and marketing to formulate strategic decision-making. Strategiesto increase production capacity were done by using the approach of theory of constraints (TOC).There are 10 stages in the process of making the ‘otak-otak bandeng’. The result shows theidentification of constraints occur in the process of separating the thorn of the fish. Replacement ofmeat grinder machine increases the efficiency of processing time by 13%. Furthermore, change ismade on the work procedures for cooling process and inserting fish in the plastic packaging bags.The replacement of meat grinder machine and changing the work procedures for packaging hassaving the processing time up to 20%.